Relationship between the interannual and intraseasonal temperature variability in Northeast China. (18th June 2021) - Li, Wenhui; Tan, Guirong; Li, Tim
Abstract: A significant negative correlation between the seasonal mean temperature anomaly and the intensity of the intraseasonal temperature oscillation in the northern winter over Northeast China is found during the time period 1959–2011. A stronger intraseasonal oscillation (ISO) is found during an extremely cold winter. The cold winter in Northeast China is a part of zonally oriented large‐scale pattern with a negative (positive) temperature anomaly in mid‐ (high) latitudes and is associated with a negative phase of the North Atlantic Oscillation (NAO). The intraseasonal temperature anomaly originates from high‐latitude Central Eurasia and propagates southeastward. The southeastward propagation is attributed to the upper tropospheric dispersion of Rossby wave energy as a result of coupling of the low‐level temperature and the upper‐level geopotential height. The cause of the negative correlation between the intraseasonal and interannual modes is investigated. A cold winter in Northeast China is associated with a weakened meridional temperature gradient and vertical wind shear north of 50°N. This weakens synoptic variability in situ through baroclinic instability. Because the ISO competes for an energy source with the synoptic motion, the ISO is enhanced north of 50°N. The southeastward propagation of the enhanced ISO mode increased intraseasonal temperature variability over Northeast China. As a result, a cold winter in Northeast China is accompanied by an enhanced ISO variability in situ. The enhanced local ISO could further feedback to the winter mean temperature anomaly through nonlinear advective processes. The diagnosis of the temperature budget indicates that the ISO may interact with motion on other scales to contribute to the winter mean temperature anomaly in situ. Abstract : This work indicates that the correlation map between the time series of the ISO intensity averaged over 38–53°N, 118–133°E and the time series of the winter temperature anomaly at all stations. Significant negative correlations appear over Northeast China. The correlation coefficient between them is −0.32, exceeding the 95% confidence level. This indicates that a significant negative correlation occurs between the winter temperature anomaly and the ISO intensity in Northeast China. A stronger (weaker) ISO variability is accompanied with a cold (warm) winter over Northeast China.